Palladium-catalysed cross-coupling reaction of ultra-stabilised 2-aryl-1,3-dihydro-1H-benzo[d]1,3,2-diazaborole compounds with aryl bromides: A direct protocol for the preparation of unsymmetrical biaryls - Sithebe, Siphamandla; Robinson, Ross S. (Beilstein Journal of Organic Chemistry, 2014)
There has been a significant interest in organoboron compounds such as arylboronic acids, arylboronate esters and potassium aryltrifluoroborate salts because they are versatile coupling partners in metal-catalysed cross-coupling reactions. On the other hand, their nitrogen analogues, namely, 1,3,2-benzodiazaborole-type compounds have been studied extensively for their intriguing absorption and fluorescence characteristics. Here we describe the first palladium-catalysed Suzuki–Miyaura cross-coupling reaction of easily accessible and ultra-stabilised 2-aryl-1,3-dihydro-1H-benzo[d]1,3,2-diazaborole derivatives with various aryl bromides. Aryl bromides bearing electron-withdrawing, electron-neutral and electron-donating substituents are reacted under the catalytic system furnishing unsymmetrical biaryl products in isolated yields of up to 96% in only 10 minutes.
Keywords: aryl bromide; 2-aryl-1,3-dihydro-1H-benzo[d]1,3,2-diazaborole; asymmetrical biaryls; microwave; Suzuki–Miyaura cross-coupling